Application of gluteus maximus fasciocutaneous V-Y advancement flap combined with resection in sacrococcygeal pressure ulcers: A CONSORT-compliant article. Issue 47 (November 2017) - Liu, Xing; Lu, Wan; Zhang, Yidong; Liu, Yun; Yang, Xinghua; Liao, Sheng; Zhang, Zhongrong
Abstract: Background: Traditional gluteus maximus myocutaneous flaps have generally been used to fill tissue defects after resection of sacrococcygeal pressure ulcers. However, postoperative complications were gradually revealed as increasing operations were performed. This study aimed to introduce the innovative application of gluteus maximus fasciocutaneous V-Y advancement flaps for repairing tissue defects and to comparatively analyze the differences between the innovative and traditional flaps. Methods: A total of 32 cases were included in this study. All the PU lesions were removed by resection. Sixteen cases used the gluteus maximus myocutaneous flaps, and the remaining 16 cases used gluteus maximus fasciocutaneous V-Y advancement flaps to fill the tissue defects after surgery. Comparative analysis between the gluteus maximus myocutaneous flaps and gluteus maximus fasciocutaneous V-Y advancement flaps was used to evaluate the 2 flaps based on the mean operating time, postoperative infection, paresthesia, appearance of flaps, and recurrence. Results: The gluteus maximus fasciocutaneous V-Y advancement flaps required a reduced operating time and a more simple operation compared with the gluteus maximus myocutaneous flaps. Although the infectious risk of the gluteus maximus fasciocutaneous V-Y advancement flaps was reduced compared with the gluteus maximus myocutaneous flaps, the gluteus maximus myocutaneous flaps have a better appearance compared with the gluteus maximus fasciocutaneous V-Y advancement flaps. Most importantly, no flap necrosis was noted, and the recurrence rate during follow-up was reduced in cases using the gluteus maximus fasciocutaneous V-Y advancement flaps. Conclusion: The combined application of gluteus maximus fasciocutaneous V-Y advancement flaps with surgical resection can reduce the postoperative complications and aid in the treatment of sacrococcygeal pressure ulcers.